Transnationalism, integration, and ethnic organizations: A study of Swedish ethnic organizations in light of the transnationalization of civil society (Sociologisk Forskning, 2021)
This article explores the activities of Swedish ethnic organizations. More specifically it explores how this organizational field has changed in light of more wide-ranging transformations of the Swedish civil society. The article is based on a study of the annual reports of ethnic organizations (N=52) that received a grant from the Swedish Agency for Youth and Civil Society (MUCF) in 2017, as well as 17 interviews with representatives of the said organizations. The study found indications of both path-dependent continuity and change. The ethnic organizations had maintained a longstanding focus on cultural activities of various kinds. Moreover, the influence of the study associations (studieförbund), and thus, the popular movement model (folkrörelsemodellen), was still substantial. In terms of change, in order to promote integration, some organizations appear to have taken on the role of service-producer, primarily to help members to navigate in relation to various Swedish public authorities. In addition, the study found that some ethnic organizations had become involved in new types of transnational governance networks with Swedish authorities, sending states, transnational migrant organizations and aid organizations. There are also indications of a “transnationalization” of opinion formation-activities in that some of them are aimed at a broader, international audience.
Keywords: integration; ethnicity; migration; civil society; popular movements